2021
DOI: 10.1002/nano.202100086
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of bacterial cellulose‐based air filter with antibacterial activity for highly efficient particulate matters removal

Abstract: Multifunctional air filters with efficient particulate matters (PMs) removal, low respiratory resistance and prevention harmful substances are highly demanded. Bacterial cellulose (BC) air filter can capture PMs and separate them from the airflow; however, the dense network structure sacrifices the air permeability. Herein, we incorporated silver nanowires (AgNW) to BC filter through in‐situ cultivation method to prepare a new air filter. The addition of AgNW endows BC filter with antibacterial activity and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…15B-D). Similar PM adsorption on air filter fibers was also observed in a nanocellulose-based air filter, 15 a hierarchically structured cellulose nanofiber/zein protein nanoparticle/ wood pulp composite air filter, 16 a bacterial-cellulose-based air filter, 60 and electrospun polymeric fiber-based air filters. 13,23 The PM capture mechanism of the CNC-coated cotton mesh air filter was proposed, and is shown in Scheme 3.…”
Section: Pm 25 Removal Efficiency Evaluationsupporting
confidence: 60%
“…15B-D). Similar PM adsorption on air filter fibers was also observed in a nanocellulose-based air filter, 15 a hierarchically structured cellulose nanofiber/zein protein nanoparticle/ wood pulp composite air filter, 16 a bacterial-cellulose-based air filter, 60 and electrospun polymeric fiber-based air filters. 13,23 The PM capture mechanism of the CNC-coated cotton mesh air filter was proposed, and is shown in Scheme 3.…”
Section: Pm 25 Removal Efficiency Evaluationsupporting
confidence: 60%
“…Multifunctional air filters for effective removal of particulate matter, prevention of dangerous materials, and low respiratory resistance are required. Air filters based on bacterial cellulose (nano-fiber secreted through Acetobacter xylinum ), capture particulate matters from airflow [ 34 ]. Nevertheless, the dense construction sacrifices air permeability.…”
Section: The Performance Of Metals Metallic Oxide and Metal Ions For ...mentioning
confidence: 99%
“…4 a: Schematic illustration of the preparation of BC/AgNW filter with antibacterial activity for highly efficient PMs removal, b: The photographs of the BC air filter paper before and after filtration test, c: Schematic illustration the as-prepared air filter paper for anti-bacteria. The filter material can effectively kill bacteria (Reprinted with permission from [ 34 ], Copyright 2021 Wiley). …”
Section: The Performance Of Metals Metallic Oxide and Metal Ions For ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The in situ cultivation method was employed for the incorporation of AgNW into the BC matrix. The high filtration efficiency of 99.7 and 99.8% for PM 2.5 and PM 10 , respectively, was attributed to the electrostatic adsorption achieved by AGNW incorporation [ 159 ]. He et al reported an even distribution of modified soy protein isolate (SPI) on BC membranes.…”
Section: Bc Applicationsmentioning
confidence: 99%